2017
DOI: 10.1186/s13054-017-1743-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome modulation by hydrocortisone in severe burn shock: ancillary analysis of a prospective randomized trial

Abstract: BackgroundDespite shortening vasopressor use in shock, hydrocortisone administration remains controversial, with potential harm to the immune system. Few studies have assessed the impact of hydrocortisone on the transcriptional response in shock, and we are lacking data on burn shock. Our objective was to assess the hydrocortisone-induced transcriptional modulation in severe burn shock, particularly modulation of the immune response.MethodsWe collected whole blood samples during a randomized controlled trial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…30 severe burn patients admitted at Hospices Civils de Lyon, France (HCL) were included in a placebo-controlled, randomized, double-blind study assessing the efficacy of hydrocortisone administration on burn shock duration. Inclusion / exclusion criteria, clinical description and ethical considerations of the cohort have been previously published elsewhere (Venet et al 2015; Plassais et al 2017). Thirteen healthy volunteers were also recruited within Hospices Civils de Lyon to serve as controls for the transcriptional study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 severe burn patients admitted at Hospices Civils de Lyon, France (HCL) were included in a placebo-controlled, randomized, double-blind study assessing the efficacy of hydrocortisone administration on burn shock duration. Inclusion / exclusion criteria, clinical description and ethical considerations of the cohort have been previously published elsewhere (Venet et al 2015; Plassais et al 2017). Thirteen healthy volunteers were also recruited within Hospices Civils de Lyon to serve as controls for the transcriptional study.…”
Section: Methodsmentioning
confidence: 99%
“…After severe injuries like septic shock, burn or trauma, leading to an important inflammatory response, we and others have shown that the blood transcriptome is highly modulated, with early and profound changes in adaptive and innate immune responses (Plassais et al 2017; Xiao et al 2011). Moreover in these contexts, viral reactivation is often observed, especially for Herpes Viruses (Ong et al 2017; Textoris and Mallet 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory response parameters are reported not only to depend on burn size but also to differ between individuals [12-16]. These differences may be explained in part by differences in each individual genetic make-up [17,18]. Burn trauma also induces coagulopathy and combining a patient's early coagulation and inflammatory status in addition to standard clinical indices improves prognostic models [19].…”
Section: Parameters Indicating the Need For Intervention To Reduce Camentioning
confidence: 99%
“…Recently however, several studies with low-dose hydrocortisone started immediately after admission were reported to improve outcome in patients with major burns [21][22][23]31,32]. Hydrocortisone differentially regulates cytokine responses and modulates transcriptional processes [18,33]. This provides a physiological understanding of the mechanism of action of hydrocortisone on cytokine responses and thus on capillary leakage.…”
Section: Hydrocortisone and Other Strategies To Decrease Capillary Lementioning
confidence: 99%
“…After severe injuries like septic shock, burn or trauma, leading to an important inflammatory response, we and others have shown that the blood transcriptome is highly modulated, with early and profound changes in adaptive and innate immune responses (16, 17). Moreover, in these contexts, viral reactivation is often observed, especially for Herpes Viruses (18, 19).…”
Section: Introductionmentioning
confidence: 99%